2005
DOI: 10.1159/000087071
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Milk Does Not Alter the Antioxidant Activity of Black Tea

Abstract: Tea is a polyphenol-rich beverage like wine and catechins are its chief polyphenols. Catechins have cardio-protective effects as they can scavenge free radicals and inhibit lipid peroxidation. Epidemiological studies indicate an inverse relation between tea consumption and the risk of cardiovascular and other chronic diseases. Addition of milk to black tea has been reported to adversely affect its beneficial effects, but the data are not unequivocal. Therefore, we assessed the effect of the addition of milk to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 90 publications
(65 reference statements)
2
60
0
Order By: Relevance
“…28 However, it should be noted that other studies failed to establish an effect of milk on antioxidant properties of tea. 29,30 The reasons for these discrepant findings are largely unknown but may be attributed to different physiological/experimental endpoints (e.g. in vitro and in vivo, and assays for measurements of antioxidant activities).…”
Section: Discussionmentioning
confidence: 99%
“…28 However, it should be noted that other studies failed to establish an effect of milk on antioxidant properties of tea. 29,30 The reasons for these discrepant findings are largely unknown but may be attributed to different physiological/experimental endpoints (e.g. in vitro and in vivo, and assays for measurements of antioxidant activities).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively some studies have shown that the addition of milk to tea inhibits its antioxidant activity whereas other workers have reported that the addition of milk does not alter the antioxidant activity of polyphenols in tea, coffee, or cocoa beverages (Richelle, Tavazzi, & Offord, 2001;Serafini, Ghiselli, & Ferro-Luzzi, 1996). Lower levels of plasma catechins have also been reported after drinking tea with milk compared to black tea (Reddy, Vidya Sagar, Sreeramulu, Venu, & Raghunath, 2005). In contrast, other workers have reported that milk had no effect on plasma levels of catechins (Van het Hof, Kivits, Weststrate, & Tijburg, 1998).…”
Section: Changes In Total Phenolic Contents After Codigesting Pomegramentioning
confidence: 98%
“…Since plasma concentrations of polyphenols in humans commonly reach 1-10 lM [25][26][27][28][29], these compounds might be expected to have a protective effect on red blood cells. Grinberg, et al have reported such protective effects for polyphenols in green and black tea against red blood cell lipid peroxidation, noting a concentration-dependent inhibitory effect on • OH production, and cytoprotection of red blood cells in vitro from primaquine-induced oxidative stress due to O 2…”
Section: Protective Effects Of Polyphenols In Blood and Plasmamentioning
confidence: 99%
“…1), which constitute up to 30% of the plant's dry leaf weight [24]. Within just 2 h after consumption of one cup of green or black tea (350-600 ml) [25][26][27][28], catechins have been found in concentrations of 0.3-1 lM in human plasma and may even approach 10 lM with higher doses [29]. Flavonols ( Fig.…”
mentioning
confidence: 99%